On the linear convergence rate of a relaxed forward–backward splitting method. (3rd June 2021) - Guo, Ke
ABSTRACT: We focus on a relaxed version of the classic forward–backward splitting method in the context of finding a zero point of the sum of two monotone operators, and derive its linear convergence rate. The proof is very short by using the recently proposed concept of negatively averaged operator.